(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The proposed article considers the issue of damage assessment and the specifics of its reflection in accounting (budget) accounting registers by accounting entities of the Ministry of Defense of the Russian Federation. This issue has been repeatedly highlighted by various authors, but it remains relevant today.